2020
DOI: 10.21873/invivo.11832
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden in Patients With Reduced Performance Status at the Start of Palliative Radiotherapy

Abstract: Background/Aim: Previous research has suggested that palliative radiotherapy is a useful measure, unless short survival reduces the time spent without active treatment, and in the case of a low likelihood of experiencing a net benefit in quality of life. Patients with reduced performance status (PS) may be especially at risk of futile treatment, despite having a relatively high symptom burden and thus a potential benefit. Therefore, we analyzed the symptom burden of patients with Eastern Cooperative Oncology G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous findings on marital status were inconsistent; some were non-significant findings while some found that widowed older adults were less likely to go to medicalized settings at the end of life. 32,33 We found that people who were divorced with children or single or never married were more likely to prefer receiving palliative care at home than those married with children. It could be the reason that Chinese people with intact families tend to feel more connected to their families, regardless of the physical location of home; in contrast, those who were not married or divorced might need to be physically at home to feel the sense of being safe and belonged.…”
Section: Discussionmentioning
confidence: 79%
“…Previous findings on marital status were inconsistent; some were non-significant findings while some found that widowed older adults were less likely to go to medicalized settings at the end of life. 32,33 We found that people who were divorced with children or single or never married were more likely to prefer receiving palliative care at home than those married with children. It could be the reason that Chinese people with intact families tend to feel more connected to their families, regardless of the physical location of home; in contrast, those who were not married or divorced might need to be physically at home to feel the sense of being safe and belonged.…”
Section: Discussionmentioning
confidence: 79%
“…Multiple prior analyses have demonstrated a relationship between PROs and survival outcomes in several different cancer populations 2,9,30‐32 . In the baseline setting, these findings may be attributed to a higher symptom burden at the initiation of systemic chemotherapy correlating with a lower performance status, a metric also previously shown to correlate with overall survival 33,34 . Patients with reduced performance status and/or higher symptom burden may be less able to tolerate therapy, thus attenuating the ability of cancer treatment to offer survival benefits 35 .…”
Section: Discussionmentioning
confidence: 99%
“…2,9,[30][31][32] In the baseline setting, these findings may be attributed to a higher symptom burden at the initiation of systemic chemotherapy correlating with a lower performance status, a metric also previously shown to correlate with overall survival. 33,34 Patients with reduced performance status and/or higher symptom burden may be less able to tolerate therapy, thus attenuating the ability of cancer treatment to offer survival benefits. 35 In addition, we found that baseline PROs are associated with unplanned hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…However, the balance between providing symptomatic relief and ensuring patient safety remains a critical concern. Patients with a limited life expectancy and a compromised performance status might not derive a net advantage from undergoing palliative radiotherapy (9). There is a pressing need for endeavors directed towards the improvement and precision of the criteria employed for determining the appropriate timing of radiotherapy initiation (10).…”
Section: Discussionmentioning
confidence: 99%